2017
DOI: 10.1080/07315724.2016.1267597
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric Supplementation Improves Serum Glucose Indices and Leptin Levels in Patients with Nonalcoholic Fatty Liver Diseases

Abstract: Turmeric supplementation improved glucose indexes and serum leptin levels and may be useful in the control of NAFLD complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 46 publications
2
114
0
Order By: Relevance
“…After reading the full text of the remaining 10 studies, four studies were also excluded for the following reasons: two studies did not report data on liver enzymes (Basu et al, ; Jazayeri‐Tehrani et al, ), one study was a duplicate report (Ghaffari, Rafraf, Navekar, & Asghari‐Jafarabadi, ), and one study was published as protocol (Jazayeri‐Tehrani et al, ). Finally, six eligible RCTs (Chirapongsathorn et al, ; Jarahzadeh & Hosain, ; Moradi et al, ; Navekar et al, ; Panahi et al, ; Rahmani et al, ) were included in our analysis. A flowchart of the systematic search and study selection process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full text of the remaining 10 studies, four studies were also excluded for the following reasons: two studies did not report data on liver enzymes (Basu et al, ; Jazayeri‐Tehrani et al, ), one study was a duplicate report (Ghaffari, Rafraf, Navekar, & Asghari‐Jafarabadi, ), and one study was published as protocol (Jazayeri‐Tehrani et al, ). Finally, six eligible RCTs (Chirapongsathorn et al, ; Jarahzadeh & Hosain, ; Moradi et al, ; Navekar et al, ; Panahi et al, ; Rahmani et al, ) were included in our analysis. A flowchart of the systematic search and study selection process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…We excluded nine other studies because of the following reasons: (a) Seven articles were derived from the same trials and reported the same outcomes. We included the most complete ones to avoid double weighting in the estimates derived from the same studies (Jazayeri‐Tehrani et al, ; Navekar et al, ; Saadati et al, ). (b) Trials without placebo or control group were excluded ( n = 2; Panahi, Kianpour, Mohtashami, Soflaei, & Sahebkar, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the overall pooled estimate of eight trials (Chashmniam et al, ; Cicero et al, ; Jazayeri‐Tehrani et al, ; Mirhafez et al, ; Navekar et al, ; Panahi et al, ; Rahmani et al, ; Saadati et al, ) with 520 participants (a dose ranging from 70 to 3,000 mg/day), it was shown that curcumin supplementation was associated with a significant reduction in BMI (WMD = −0.34 kg/m 2 , 95% CI [−0.64, −0.04], p < .05) compared with the control group (Figure ). The heterogeneity among trials investigating the effect of curcumin supplementation on BMI was high ( I 2 = 63.2%, p < .01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations